Cardiovascular disease and diabetes mellitus in Norway during 1994-2009 CVDNOR – a nationwide research project - Gerhard Sulo; Jannicke Igland; Dan J. Stein; Ottar Nygård; Nina Øyen; Grethe S. Tell (2013)
Background: Although having a long tradition in cardiovascular epidemiologic research, nationwide data on cardiovascular disease (CVD) incidence and morbidity has not been available in Norway. Objectives: The main objectives of The Cardiovascular Disease in Norway (CVDNOR) project are 1) to study trends in CVD incidence, prevalence, survival and mortality and 2) providing CVD endpoints for national and regional health surveys and clinical studies. Methods: CVDNOR includes information from all hospital stays with a CVD, including congenital heart defects, or diabetes mellitus (DM) primary or secondary diagnosis code during 1994-2009. Information was retrieved from the electronic Patient Administrative Systems (PAS) from all Norwegian somatic hospitals. Data include age, gender, municipality of residence, hospitalization and discharge dates, main and secondary diagnoses and CVD-related procedure codes. All deaths due to CVD or DM are also included, as well as sociodemographic information and linkage to Cohort Norway (CONOR). In sub-projects we have also linked CVDNOR to the Medical Birth Registry of Norway and to the Cancer Registry. Results: During 1994-2009, 1.3 million patients (4.3 mill hospitalizations) had a CVD diagnosis or procedure code, or DM. Of these, 470895 (35.8%) died during 1994-2010. In addition, 68523 men and women died from CVD without being hospitalized for CVD or DM during the same period. Among 173243 CONOR participants, 9075 (5%) died after participating in the health survey and through 2010. A total of 44118 (25.5%) CONOR participants had a CVD and 7575 (4.4%) had a DM related hospitalization after participating in CONOR, through 2009. In CVDNOR, 53039 (4%) had congenital heart defect codes. Conclusions: CVDNOR will be a valuable source of information supporting future epidemiologic research, with important implications for prevention and treatment strategies.